2010
DOI: 10.1088/1748-3182/5/1/016004
|View full text |Cite
|
Sign up to set email alerts
|

The role of intrinsic muscle properties for stable hopping—stability is achieved by the force–velocity relation

Abstract: A reductionist approach was presented to investigate which level of detail of the physiological muscle is required for stable locomotion. Periodic movements of a simplified one-dimensional hopping model with a Hill-type muscle (one contractile element, neither serial nor parallel elastic elements) were analyzed. Force-length and force-velocity relations of the muscle were varied in three levels of approximation (constant, linear and Hill-shaped nonlinear) resulting in nine different hopping models of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
109
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(118 citation statements)
references
References 39 publications
9
109
0
Order By: Relevance
“…While the most reduced models of walking and running -compass gait model and spring mass model -showed that stable walking is possible without the need for any adaptation (Blickhan, 1989;Garcia et al, 1998;Geyer et al, 2006;Goswami et al, 1998;Seyfarth et al, 2002;Srinivasan and Ruina, 2006), some of their offspring models emphasize the benefit of feed-forward timed adaptation of leg characteristics (Birn-Jeffery and Daley, 2012;Blum et al, 2010;Ernst et al, 2012;Karssen et al, 2011) and muscle activity (Haeufle et al, 2010) for the stabilization of locomotion patterns. As our results clearly indicate such a time-dependent feed-forward change in muscle activity in the absence of visual feedback (Fig.…”
Section: Research Articlementioning
confidence: 99%
“…While the most reduced models of walking and running -compass gait model and spring mass model -showed that stable walking is possible without the need for any adaptation (Blickhan, 1989;Garcia et al, 1998;Geyer et al, 2006;Goswami et al, 1998;Seyfarth et al, 2002;Srinivasan and Ruina, 2006), some of their offspring models emphasize the benefit of feed-forward timed adaptation of leg characteristics (Birn-Jeffery and Daley, 2012;Blum et al, 2010;Ernst et al, 2012;Karssen et al, 2011) and muscle activity (Haeufle et al, 2010) for the stabilization of locomotion patterns. As our results clearly indicate such a time-dependent feed-forward change in muscle activity in the absence of visual feedback (Fig.…”
Section: Research Articlementioning
confidence: 99%
“…More precisely, the higher MC in the MusFib model can be attributed to the force-velocity characteristics of the muscle fibers. Previous hopping simulations showed that these non-linear contraction dynamics reduce the influence of the controller on the actual hopping kinematics (Haeufle et al, 2010(Haeufle et al, , 2012. This means, that the kinematic trajectory is more predetermined by the material properties as compared to the linearized muscle model MusLin, or the motor model DCMot.…”
Section: Discussionmentioning
confidence: 99%
“…In a reduced model, hopping motions can be described by a one-dimensional differential equation (Haeufle et al, 2010):…”
Section: Hopping Modelsmentioning
confidence: 99%
See 2 more Smart Citations